Simultaneously comparing various CO2-mineralized steelmaking slags as supplementary cementitious materials via high gravity carbonation - Tse-Lun Chen; Bo-Kai Shu; Yi-Hung Chen; Pen-Chi Chiang (Journal of CO2 Utilization)
The integration of accelerated carbonation with the utilization of steelmaking slags presents a vital strategy for CO2 mineralization towards net-zero scheme. This study simultaneously evaluates basic oxygen furnace slag (BOFS), refining slag (RFS), and electric arc furnace reducing (EAFRS) and oxidizing slags (EAFOS) as potential partial replacements for ordinary Portland cement, at substitution levels ranging from 5 % to 15 % as supplementary cementitious materials (SCMs). These slags were pretreated through aqueous accelerated carbonation in a high-gravity rotating packed bed. We assessed several parameters, including carbonation conversion, CO2 capture capacity, workability, strength, and durability. The results demonstrated that EAFRS achieved the highest CO2 capture capacity, reaching 0.193 kg-CO2/kg-slag with a maximum carbonation conversion of 46 % under 197 times high-gravity conditions and a liquid-to-solid ratio of 20. While the incorporation of carbonated slags had minimal impact on the setting properties of cement pastes, higher substitution ratios necessitated increased water demand. The strength of blended cement containing 5 %, 10 %, and 15 % of carbonated BOFS, RFS, and EAFRS met standard requirements at 28th day. Additionally, a mathematical model was developed to predict the mechanical strength of cement mortars. The introduction of carbonated BOFS, RFS, and EAFRS facilitated hydration due to the formation of calcium carbonates, although it resulted in slower strength development kinetics. Notably, the replacement of cement with carbonated EAFOS exhibited a higher expansion rate, likely due to its elevated silicon dioxide and alkaline species content, which may lead to alkali-aggregate reactions, resulting in expansion and cracking.